IL‐18R signaling is required for γδ T cell response and confers resistance to Trypanosoma cruzi infection. Issue 4 (25th May 2020) - da Mota, Julia Barbalho; Echevarria‐Lima, Juliana; Kyle‐Cezar, Fernanda; Melo, Matheus; Bellio, Maria; Scharfstein, Julio; Oliveira, Ana Carolina
Abstract: IFN‐γ‐producing γδ T cells have been suggested to play an important role in protection against infection with Trypanosoma cruzi . However, little is known about the mechanisms leading to functional differentiation of this T cell subset in this model. In the current work, we investigated the possibility that the IL‐18/MyD88 pathway is central for the generation of effector γδ T cells, playing a role for resistance against infection. We found that splenic γδ + CD3 + cells were rapidly expanded (10–14 days post infection), which was accompanied by an early γδ T cell infiltration into the heart. In the following days, intracardiac parasitism was reduced, the protective immunity being accompanied by decreased γδ T cells tissue infiltration. As predicted, there was a drastic reduction of γδ T cells in Myd88 ‐ and Il18r1 ‐deficient mice, both transgenic strains displaying a susceptible phenotype with increased intracardiac parasitism. In vivo and in vitro assays confirmed that IL‐18R deficiency hampered γδ T cell proliferation. Further characterization revealed that T. cruzi infection up‐regulates IL‐18R expression in WT γδ + T cell population whereas Il18r1 −/− mice showed impaired generation of cytotoxic GzB + and IFN‐γ‐producing γδ T cells. Consistently, in vitro cytotoxicity assay confirmed that cytolytic function was impaired in Il18r1 ‐deficient γδ T cells. As a proof of concept, adoptive transfer of WT γδ T cells rescues Il18r1 ‐deficient mice from susceptibility, reducing parasitemia and abrogating the mortality. Collectively, our findings implicate the IL‐18R‐MyD88 signaling in the mechanisms underlying generation of immunoprotective γδ T cells response in experimental Trypanosoma cruzi infection. Graphical Abstract: Effector γδ T cells contribute to resistance to experimental Chagas' disease induced by Trypanosoma cruzi in an MyD88‐IL‐18R‐dependent manner.